PENGARUH VITAMIN C TERHADAP KADAR SERUM FERITIN PADA PASIEN GAGAL GINJAL KRONIK DENGAN HEMODILISIS REGULER - Wiryani, Cilik; Suwitra, Ketut (journal of internal medicine; Vol. 11, No. 2 Mei 2010)
Hyperferitinemia in chronic kidney disease patients with regular hemodyalisis may caused by repeated transfusion, excessive iron supplementations, and also inß ammation. Increasing of serum feritin level doesn!t depend on iron reserve capacity. Hemodialysis patients with no supplementations may lead to several antioxidant components deÞ ciency. Qualitative and quantitative of vitamin C deÞ ciency may also occur, thus administration 1 " 1.5 gram/week or 300 mg of vitamin C parenterally every dialysis session was recommended in order to compensate subclinical deÞ ciency. This study determine whether administration of vitamin C (500 mg, in NaCl 0.9%, every session of hemodialysis in 8 weeks) can decrease serum feritin level in chronic kidney disease patients with regular hemodialysis. Randomized clinical trial, single-blind of 38 chronic kidney disease patients with regular hemodialysis was recruited based on inclusion and exclusion criteria. Randomization in group with treatment was done with permuted block randomization. Mean of serum feritin before and after treatment in every group was compared and analysed with Man-Whitney U test. SigniÞ cancy level () was with p less than 0.05 (p < 0.05). The result of median and mean for decreasing of serum feritin in group with treatment of 500 mg, vitamin C is 0.00 (-227.00 " 218.00) and 77.85 ± 383.25, respectively. While the result of median and mean for decreasing of serum feritin control group is 32.00 (-14.00 " 108.00) and 65.85 ± 209.6, respectively. On the analysis indicates median of serum feritin in group with treatment of vitamin C had less 32 points depends with control group (p = 0.84), Thus, there was no signiÞ cant difference (p > 0.05) between two groups. From Anova analysis for gender, there was signiÞ cant effect in decreasing of serum feritin level (p < 0.05). There was no decreasing of serum feritin level after administration of 500 mg, vitamin C in chronic kidney disease patients with regular hemodialysis, and sex had signiÞ cant effect in alteration of serum feritin level.
Keywords: chronic kidney disease, reguler haemodyalisis, hyperferitinemia, vitamin C